Conflict, disasters and no jobs: Reasons for international migration from Sub-Saharan Africa - Wim Naudé (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
Sub-Saharan Africa (SSA) has the highest growth rate in net international migration in the world. The reasons for this migration are investigated in this paper. First, a survey of the literature on the profile and determinants of international migration in SSA is given. Second, panel data on 45 countries spanning the period 1965 to 2005 are used to determine that the main reasons for international migration from SSA are armed conflict and lack of job opportunities. An additional year of conflict will raise net out-migration by 1.35 per 1,000 inhabitants and an additional 1 per cent growth will reduce net outmigration by 1.31 per 1,000. Demographic and environmental pressures have a less important direct impact, but a more pronounced indirect impact on migration through conflict and job opportunities. In particular, the frequency of natural disasters has a positive and significant effect on the probability that a country will experience an outbreak of armed conflict. Furthermore, there is no evidence of a migration hump or of persistence in net migration rates in SSA, and no evidence that immigration is causing conflict in host countries.
Keywords: F22; J61; O15; R23; Q34; Q54; 330; international migration; conflict; natural disasters; environmental degradation; environmentally forced migration; Africa; Internationale Wanderung; Auswanderung; Politischer Konflikt; Naturkatastrophe; Umweltbelastung; Afrika südlich der Sahara